A summary of the best evidence for story therapy to delay cognitive decline in the elder-ly with mild to moderate cognitive impairment - Chen SUN; Zheng-Gang BAI (Yixue xinzhi zazhi)
Objective To evaluate and summarize the best evidence for the use of story therapy to delay cognitive decline in elderly with mild to moderate cognitive impairment.Methods UpToDate, SIGN, NZGG, Cochrane Library, Yimaitong, Embase, PubMed, CNKI, WanFang, and VIP databases were computer searched from January 1, 2010 to February 25, 2022 for all guidelines on story therapy for delaying cognitive decline in the elderly with mild to moderate cognitive impairment. Evidence summaries, best practice information books, recommended practices, systematic reviews, expert opinion, randomized controlled trials, and qua-si-experimental studies were all included. Appropriate quality assessment tools were used to evaluate the included literature, and to summarize the best evidence on story therapy for delaying cognitive decline in older adults with mild to moderate cognitive impairment.Results A total of 16 articles were included: 4 sys-tematic reviews, 9 randomized controlled trials, and 3 quasi-experimental studies. After evaluation, a total of 33 most important factors for delaying cognitive decline in the elderly with mild to moderate cognitive impair-ment were summarized, including story therapy type, activity form, venue selection, material preparation, in-tervention time, intervention process, precautions, and promotion and application.Conclusions This study summarizes the current best evidence on story therapy for delaying cognitive decline in the elderly with mild to moderate cognitive impairment, and provides practical reference for the practice of non-drug interventions for this group of patients.